2017
DOI: 10.1021/acs.energyfuels.7b01771
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of CaS–CaO Oxidation for Chemical Looping Combustion with a CaSO4-Based Oxygen Carrier

Abstract: The oxidation of CaS to a CaSO 4 oxygen carrier suffers SO 2 release. To capture SO 2 released, an amount of CaO particles was mixed with CaS particles. Isothermal kinetics of the CaS−CaO oxidation reaction has been conducted in a thermogravimetric reactor combined with a Frourier transform infrared spectroscopy (FTIR) analyzer. The effects of the reaction temperature, O 2 concentration, and molar ratio of CaO/CaS on CaSO 4 generation and SO 2 emission were investigated. The chemical compositions, morphology s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…What is worse is that increasing the operating temperature would singly exacerbate the emission of sulfur from CaSO 4 via the side reactions of eqs 1−5 below. 13,14 Sulfur released not only led to atmospheric pollution but also tarnished the purity of outlet CO 2 and declined the reactivity of CaSO 4 .…”
Section: Introductionmentioning
confidence: 99%
“…What is worse is that increasing the operating temperature would singly exacerbate the emission of sulfur from CaSO 4 via the side reactions of eqs 1−5 below. 13,14 Sulfur released not only led to atmospheric pollution but also tarnished the purity of outlet CO 2 and declined the reactivity of CaSO 4 .…”
Section: Introductionmentioning
confidence: 99%
“…The preparation of oxygen carriers is similar to our previous studies [23]. The analytical CaSO4 (Tianjin Fuchen Chemical Factory) and the analytical CuO (Guangdong Guanghua Science and Technology CO., Ltd.) particles were used in this work.…”
Section: Preparation Of Oxygen Carriersmentioning
confidence: 89%
“…In our previous studies, the addition of https://doi.org/10.37358/RC. 21.3.8443 CaO not only achieved high CO2 production efficiency, but also inhibited the side reaction of CaSO4 and prevented the emission of gaseous sulfur [23]. Wang et al [24] reported to use the CaSO4-CuO as an mixed OC for the coal-fueled CLC and confirmed its feasibility.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, the overall reaction process can be described with the shrinking core model. Furthermore, the high Ca/S ratio can inhibit the sulfur release. , When coal is used as the fuel, the gasification influences the whole reaction and the ability of the oxygen-transmitting capacity is about 4 times as much as other cheap OCs, such as ilmenite . Although the reaction rate of the char–OC reaction is slower than the gas–OC reaction, it still affects the overall reaction.…”
Section: Introductionmentioning
confidence: 99%